Bank-Specific Factors and Macroeconomic Factors in the Financial Performance of Commercial Banks in Nepal (Pravaha, 2024)
This study examines the macroeconomic and bank-specific elements that affect Nepal's commercial banks' financial performance. The financial information used in the study was taken from the 2012–2021 annual reports of the sampled banks. It covers the nine commercial banks that are active in Nepal at the time of the study. Descriptive and causal research designs were employed in the study. The performance of banks is evaluated using ROA, ROE, and NIM. The GDP growth rate and inflation rate are used as stand-ins for macroeconomic indicators. Credit risk, size, liquidity, asset quality, managerial effectiveness, and capital adequacy are the main internal elements affecting bank success. Financial ratios have been utilized in this study to analyze the banks' profitability. Bank-specific characteristics are also measured using financial ratios. The impact of macroeconomic and bank-specific factors on bank performance has been determined using a regression model. Banks have decreased their credit risk by decreasing non-performing assets. Because of the generally positive annual increase in GDP, the macroeconomic variable known as GPD has benefited the banks. Inflation and GDP have suffered over the past two years as a result of the COVID-19 pandemic. The top banks in terms of financial performance are NABIL, ADBL, and SCBN. The key factors influencing the profitability of Nepalese commercial banks include management effectiveness, capital base, credit risk, GDP, and inflation, according to the results of the regression study. Commercial banks' performance as assessed by ROA and NIM would improve with increased management efficiency. Commercial banks' performance as evaluated by ROE would improve with increases in capital base, liquidity, managerial effectiveness, and credit risk. In a similar vein, commercial banks' profitability is supported by GDP and inflation rates.